Ethics and Professional Responsibilities of Judges in Carrying Out Duties in Law Enforcement - Yeti Kurniati; Yuninda Dwi Kartika; Yoga Gustiadi; Gede Indra Udayana; Andhika Nugraha Bhakti Agung (Rechtsvinding, 2026)
The Judicial Code of Ethics serves as the ethical principles of judges, serving as the basis or guideline for every decision-making process in legal cases before them, as law enforcement officers, and in addressing the challenges of legal issues and legal developments. The purpose of this article is to provide the wider public with knowledge and understanding regarding ethics as a guideline and the challenges faced by judges in examining, adjudicating, and deciding legal cases. This article was written using literature and secondary data. The approach used in this research is the statutory approach. Judges are functional and state officials authorized to examine, adjudicate, and decide legal cases fairly and based on the law. Judges are responsible for interpreting and applying applicable law to cases before them and ensuring that justice and truth are achieved. The Judicial Code of Ethics is a written rule or code of conduct that judges must adhere to in carrying out their duties to ensure integrity, fairness, and public trust in the judicial institution. The Code of Ethics for the Judges' Professionalism contains the obligation and requirement to carry out their profession responsibly for the results and impacts of their actions and to refrain from violating the rights of others. The Code of Ethics is not law, but rather a norm that serves as a benchmark for legal professionals in upholding the authority of the law with humanity and justice. (Drs. H. Wildan Suyuthi Mustofa, "Judge's Code of Ethics," p. 52, Publisher: Jakarta, Kencana Prenada Media 2013.) The Code of Ethics for Judges is regulated by Joint Decrees of the Chief Justice of the Supreme Court of the Republic of Indonesia and the Chairman of the Judicial Commission of the Republic of Indonesia Number 047/KMA/SKB/IV/2009 and 02/SKB/P.KY/IV/2009 concerning the Code of Ethics and Guidelines for Judges' Conduct. However, in their role as legal advocates, judges often face various ethical dilemmas in making legal decisions. These dilemmas can influence the decision-making process and the final outcome of a case. As a legal advocate, a judge is often faced with various ethical dilemmas in making decisions that ultimately resolve issues. Judges are often faced with situations where the strict application of the law does not always align with the principles of justice. This helps prevent arbitrary action and ensures that the law is applied consistently.